Microbial Pathogens Trigger Host DNA Double-Strand Breaks Whose Abundance Is Reduced by Plant Defense Responses - Song, Junqi (Public Library of Science, 2014)
Immune responses and DNA damage repair are two fundamental processes that have been characterized extensively, but the links between them remain largely unknown. We report that multiple bacterial, fungal and oomycete plant pathogen species induce double-strand breaks (DSBs) in host plant DNA. DNA damage detected by histone γ-H2AX abundance or DNA comet assays arose hours before the disease-associated necrosis caused by virulent Pseudomonas syringae pv. tomato. Necrosis-inducing paraquat did not cause detectable DSBs at similar stages after application. Non-pathogenic E. coli and Pseudomonas fluorescens bacteria also did not induce DSBs. Elevation of reactive oxygen species (ROS) is common during plant immune responses, ROS are known DNA damaging agents, and the infection-induced host ROS burst has been implicated as a cause of host DNA damage in animal studies. However, we found that DSB formation in Arabidopsis in response to P. syringae infection still occurs in the absence of the infection-associated oxidative burst mediated by AtrbohD and AtrbohF. Plant MAMP receptor stimulation or application of defense-activating salicylic acid or jasmonic acid failed to induce a detectable level of DSBs in the absence of introduced pathogens, further suggesting that pathogen activities beyond host defense activation cause infection-induced DNA damage. The abundance of infection-induced DSBs was reduced by salicylic acid and NPR1-mediated defenses, and by certain R gene-mediated defenses. Infection-induced formation of γ-H2AX still occurred in Arabidopsis atr/atm double mutants, suggesting the presence of an alternative mediator of pathogen-induced H2AX phosphorylation. In summary, pathogenic microorganisms can induce plant DNA damage. Plant defense mechanisms help to suppress rather than promote this damage, thereby contributing to the maintenance of genome integrity in somatic tissues.